Structural and Conceptual Features of the Existential Discourse in the Literary Text (on the basis of the Story by A.P. Chekhov “The Duel”) (Proceedings of Southern Federal University. Philology, 2019)
Marianna B. Samoilova, Nina A. Ranneva (Rostov-on-Don, Russian Federation)The article discusses the features of the artistic reflection of philosophical meanings, objectified in existential discourse in the prose of A.P. Chekhov. The structural and conceptual dominants of everyday communication are studied.Key words: existential discourse, communicative accuracy, emotional accuracy, generalization, maxim, aphorism, script.DOI 10.23683/1995-0640-2019-1-42-47